Building material naturalness: Perceptions from Finland, Norway and Slovenia. Issue 1 (January 2017) - Burnard, Michael D.; Nyrud, Anders Q.; Bysheim, Kristian; Kutnar, Andreja; Vahtikari, Katja; Hughes, Mark
Natural elements, life and life-like processes, as well as representations of them, can produce positive experiences within the built environment. Over the past decade, a number of empirical studies have found experiencing nature, both actively and passively, can reduce stress, increase human well-being, and produce positive emotional experiences. Therefore, in this study, user perceptions of building material naturalness in three European countries, Finland, Norway, and Slovenia were investigated. A survey was conducted in each country to gather user perceptions of the naturalness of 22 building materials. Perceptions were collected in three ways: a binary decision task (e.g. natural or not natural), a seven-point scale from not natural to natural, and an ordered ranking of all specimens from most natural to least natural. The building materials included solid wood, engineered wood-based products, masonry, stone, wallpaper, ceramic tiles, metal, and plastic. Solid wood, stone, and brick were clearly considered more natural than their counterparts with greater degrees of processing. Similarly, wood-based composites with greater degrees of processing were identified as being less natural than materials with less processing. Furthermore, the study found there was agreement between regions on building material naturalness, despite some minor differences.